Re-examining the link between fairness and commitment in buyer-supplier relationships. Issue 4 (October 2017) - Jokela, Päivi; Söderman, Anne
Abstract: By re-examining the link between fairness and commitment in supply chain relationships, this study elaborates on the existing theory that views fairness only as an antecedent. It proposes that commitment can also precede perceived fairness, thus redefining the link between the concepts as bidirectional in buyer–supplier relationships. The study examines both the buyer and supplier perspectives. Based on interviews at 24 technology industry firms in Finland, this empirical study demonstrates that buyer commitment has a positive impact on how suppliers perceive distributive fairness in the relationship. In turn, this effect is reciprocated by the suppliers through a commitment in the form of relationship-specific investments and continuous improvements that are perceived as fair by the buyer. As a managerial implication the study emphasizes the importance of fairness evaluation to the relationship parties. Highlights: Bidirectional relationship between fairness and commitment is proposed. Buyer commitment increases the level of distributive fairness perceived by suppliers. Buyer evaluates supplier commitment through supplier's interest in innovation. High level of commitment to innovation is perceived as distributive fairness by the buyer. Lack of distributive fairness impedes supplier development and leads to a low level commitment.